2018
DOI: 10.1117/1.jbo.23.2.025001
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the contribution of Rayleigh scattering to the bluish appearance of veins

Abstract: The bluish appearance of veins located immediately beneath the skin has long been a topic of interest for biomedical optics researchers. Despite this interest, a thorough identification of the specific optical processes responsible for this phenomenon remains to be achieved. We employ controlled in silico experiments to address this enduring open problem. Our experiments, which are supported by measured data available in the scientific literature, are performed using first-principles models of light interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…In this type of scattering, structures such as chromophores smaller in magnitude than the wavelength of the light being emitted have a more prominent scattering effect at the blue end of the visible spectrum. 53,54 Scattering leads to less absorption by targeted chromophores and less light penetration to deeper layers of the skin. This explains why red light is able to penetrate 4-5 mm below the skin, while blue light is only able to penetrate 1 mm below the skin.…”
Section: Wavelengthmentioning
confidence: 99%
See 1 more Smart Citation
“…In this type of scattering, structures such as chromophores smaller in magnitude than the wavelength of the light being emitted have a more prominent scattering effect at the blue end of the visible spectrum. 53,54 Scattering leads to less absorption by targeted chromophores and less light penetration to deeper layers of the skin. This explains why red light is able to penetrate 4-5 mm below the skin, while blue light is only able to penetrate 1 mm below the skin.…”
Section: Wavelengthmentioning
confidence: 99%
“…It has been suggested that Rayleigh scattering accounts for the blue coloration of veins. In this type of scattering, structures such as chromophores smaller in magnitude than the wavelength of the light being emitted have a more prominent scattering effect at the blue end of the visible spectrum 53,54 . Scattering leads to less absorption by targeted chromophores and less light penetration to deeper layers of the skin.…”
Section: Mechanisms Of Iplmentioning
confidence: 99%
“…Leeuwen et al postulated that the Rayleigh scattering of skin has a major influence on the typical bluish color of veins. 3 By comparing Figs. 9(c) and 9(d), one can clearly see that even a λ −1.5 dependency of μ 0 s ðλÞ leads to a bluish appearance of the vessel.…”
Section: Spectral Dependency Of the Reduced Scattering Coefficientmentioning
confidence: 99%
“…Recently, it was postulated that Rayleigh scattering in the skin has a major impact on the bluish appearance of blood vessels. 3 Studies of other authors focused on related topics, for example, the multiple influences on the color appearance of skin, such as melanin concentration as well as different melanin types, the oiliness of skin or the blood concentration in skin. 4,5 Besides the interests to render skin correctly, diagnostics methods, such as the evaluation of erythema for different skin types, efficient port wine stain treatment, or forensic applications, where the colors of bruises are studied, also benefit from the understanding of light propagation in human skin.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, both models compute the corresponding Rayleigh scattering coefficient as a function of the fibril's radius and then adjust the direction of light propagating in this tissue accordingly. These features proved to be essential for the identification of the biophysical mechanisms responsible for the bluish appearance of cyanotic skin [BVC17] and subcutaneous veins [SRVL18].…”
Section: Stochastic Biophysically Based Modelsmentioning
confidence: 99%